THE EFFECT OF ADDING DRIED MORINGA OLEIFERA L. ON PHYSICOCHEMICAL CHARACTERISTICS AND ORGANOLEPTICS PROPERTY CRACKERS - Nisfi, Lailatun; Maghfiroh, Khoirin (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2024)
Moringa oleifera L. leaf contain energy, fat, protein, carbohydrates, fiber, vitamin A, and vitamin C. Crackers are a processed food made from a hard dough. The addition of dried Moringa oleifera L. leaf is expected to enhance the nutritional value and turn crackers into a functional food with benefits. This study aims to determine the influence of adding dried Moringa oleifera L. leaf on the antioxidant content and organoleptic properties, including taste, color, aroma, and texture of the crackers. The research was conducted at the Food Processing and Biochemistry Laboratory of Yudharta University, Pasuruan, and then Nutrition Laboratory of Airlangga University Surabaya and  then Basic Laboratory of chemistry and biology of Hang tuah University Surabaya. from April to June 2023. The research method employed a Completely Randomized Design with six treatments (0%, 5%, 10%, 15%, 20%, and 30%) repeated three times, resulting in 18 experiments. Physicochemicals data analysis used Minitab software to conduct Analysis of Variance, and Tukey Method was applied for notation determination. Organoleptic testing employed the Friedman test, while the best treatment was determined using the modified De Garmo Effective Index test by Susrini (2003). The results indicate that the addition of dried Moringa oleifera L. leaf significantly affected (p<0.05) the antioxidant activity, taste, color, aroma, and texture of the crackers. The best treatment was P1 (195 grams of dried moringa oleifera: 5 grams of dried Moringa oleifera L. leaf ) with an antioxidant activity of 91.1% Breaking power of 3.67%, moisture content of 5.98%, ash content of 3.3%,and high organoleptic values for taste 3,64%, aroma 4,32%, color 4,32%, and texture 4,08%. The addition of moringa oleifera L. leaf to crackers can enhance the nutritional value of the crackers.